2012
DOI: 10.4103/2045-080x.106259
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacy practice in Pakistan

Abstract: Objectives: This study was planned to determine the extent to which the role of a pharmacists is established in community pharmacies in Pakistan and to determine the need of qualified and experienced pharmacists in provision of healthcare at these medical stores or so called community pharmacies. Materials and Methods: A structured questionnaire was distributed to a random sample of 175 attendants at various medical stores located in different areas of Karachi with a response rate of 90.28%. Questionnaire cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Both phases of this study identified almost similar findings. The study identified that there was a lack of provision of pharmaceutical care services to the patients in Pakistan, since the patients did not report the occurrence of adverse drug reactions to the pharmacists that supported the study conducted in Karachi [14], according to which majority of pharmacists stated that the patients are not informing them about adverse drug reaction events. The present study also revealed that there was a lack of communication among hospital pharmacists and physicians in relation to drug information that was consistent with a previous qualitative study carried out in Punjab Province of Pakistan [15].…”
Section: Resultsmentioning
confidence: 99%
“…Both phases of this study identified almost similar findings. The study identified that there was a lack of provision of pharmaceutical care services to the patients in Pakistan, since the patients did not report the occurrence of adverse drug reactions to the pharmacists that supported the study conducted in Karachi [14], according to which majority of pharmacists stated that the patients are not informing them about adverse drug reaction events. The present study also revealed that there was a lack of communication among hospital pharmacists and physicians in relation to drug information that was consistent with a previous qualitative study carried out in Punjab Province of Pakistan [15].…”
Section: Resultsmentioning
confidence: 99%
“…The overall process of prescription handling, history taking and medication counselling is either limited, only few pharmacies offer, or seldom present in majority of pharmacies [ 22 , 65 ]. Provision of proper records of patients in integrated manner should be maintained and made mandatory by the government at each community pharmacy to serve the society in a better way [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, majority of community pharmacists are unaware of the concept of extended pharmacy services [ 24 ]. There is lack of awareness in public about the role of community pharmacist as well as the collaboration among the healthcare professionals, as pharmacist-physician interaction is not there in appreciable extent [ 25 ].…”
Section: Introductionmentioning
confidence: 99%